2015
DOI: 10.2527/jas.2014-8848
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of endophyte-infected ryegrass hay containing high ergovaline level in lactating ewes1

Abstract: The symbiotic association of var. (formerly named ) with perennial ryegrass () leads to the production of ergovaline (EV) and lolitrem B (LB) that are toxic for livestock. The objectives of this study were to determine the effects of feeding endophyte-infected ryegrass (SE+) hay on 16 lactating ewes (BW 80 ± 10 kg) in comparison with endophyte-free ryegrass (SE-) hay to investigate the putative mechanisms of action of EV and LB and to evaluate their persistence in milk and animal tissues. The mean EV and LB co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 48 publications
2
29
1
1
Order By: Relevance
“…Decreased plasma melatonin in E+, which would be consistent with the findings here, has been reported (Porter et al, 1993). AFMK is the product of the reaction between melatonin and reactive oxygen species (ROS; de Almeida et al, 2003;Hardeland et al, 1995;Tan et al, 2000), and previous reports found widespread decreased antioxidant defense mechanisms due to E+ (Lakritz et al, 2002;Settivari et al, 2008;Zbib et al, 2014Zbib et al, , 2015. Thus, increased AFMK may indicate early compensatory mechanism utilizing melatonin for the mitigation of E+-induced oxidative stress.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 3 more Smart Citations
“…Decreased plasma melatonin in E+, which would be consistent with the findings here, has been reported (Porter et al, 1993). AFMK is the product of the reaction between melatonin and reactive oxygen species (ROS; de Almeida et al, 2003;Hardeland et al, 1995;Tan et al, 2000), and previous reports found widespread decreased antioxidant defense mechanisms due to E+ (Lakritz et al, 2002;Settivari et al, 2008;Zbib et al, 2014Zbib et al, , 2015. Thus, increased AFMK may indicate early compensatory mechanism utilizing melatonin for the mitigation of E+-induced oxidative stress.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Plant ergot alkaloid levels are influenced by numerous abiotic factors (Guerre, 2015), and E+ EA levels here were slightly lower than previous summer studies (Hill et al, 2000). This is expected, however, as warming increases E+ alkaloid content (McCulley et al, 2014).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These authors concluded that milk is a minor route of excretion for intact ergovaline. In a separate study, ergovaline-containing perennial ryegrass hay (0.851 mg/g) was fed to lactating ewes for 28 days and ergovaline was detected in milk collected from some (but not all) of the exposed ewes, but all detectable concentrations were below the concentrations of quantitation (Zbib et al 2015). Schumann et al (2009) fed cows an ergot alkaloidcontaminated diet and did not detect any ergot alkaloids in the subsequent milk samples evaluated.…”
Section: Bioaccumulation and Excretion Of Ergovalinementioning
confidence: 95%